2022
DOI: 10.3390/ijerph19042003
|View full text |Cite
|
Sign up to set email alerts
|

Patient Participation and the Environment: A Scoping Review of Instruments

Abstract: Patient participation and the environment are critical factors in achieving qualitative healthcare. We conducted a systematic scoping review using Arksey and O’Malley’s framework to identify instruments intended to measure patient participation. We assessed those instruments’ characteristics, which areas of the healthcare continuum they target, and whether environmental factors are considered. Instruments were considered eligible if they represented the patient perspective and measured patient participation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
(159 reference statements)
0
1
0
Order By: Relevance
“…The model prioritizes patients as the focal point of the system and employs patient-centered outcome research theory to elucidate how individualized patient activation and empowerment may be achieved [76]. Furthermore, the environment encompasses a wide range of elements that might either impede or facilitate patients' engagement, performance, and entitlement to preserve their dignity [77]. For example, the International Classification of Functioning, Disability, and Health (ICF) defines environmental factors as "those that constitute the physical, social, and behavioral environment in which people live and lead their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model prioritizes patients as the focal point of the system and employs patient-centered outcome research theory to elucidate how individualized patient activation and empowerment may be achieved [76]. Furthermore, the environment encompasses a wide range of elements that might either impede or facilitate patients' engagement, performance, and entitlement to preserve their dignity [77]. For example, the International Classification of Functioning, Disability, and Health (ICF) defines environmental factors as "those that constitute the physical, social, and behavioral environment in which people live and lead their lives.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the environment on an individual's life and ability to function depends on the degree of support or demand (e.g., accessibility, usability) that the physical environment may have [78]. For example, person-environment adaptation theories explain that the adequacy of the fit between a person's functional abilities and their environment can affect a person's level of independence, participation, and overall health and well-being [77]. In our research, it was seen that patient activation levels of clients with vision loss were related to the environment sub-dimension of quality of life and that the environment was an effective factor in the established regression model.…”
Section: Discussionmentioning
confidence: 99%
“…The physical home environment is seldom considered, and it might be easier to address environmental factors when the practitioners meet the person at home when they can observe the environment as the person moves around and performs daily activities ( Kylén et al, 2021 ). However, a recent review of instruments aiming to measure patient participation in healthcare ( Kylén et al, 2022 ) revealed that few reflected participation and environmental aspects. In fact, the authors did not find a single patient reported instrument that incorporated the physical home environment as part of patient participation.…”
Section: Discussionmentioning
confidence: 99%